Evaluasi Pertumbuhan Pasar Reits Di Singapura, Malaysia, Thailand, & Hongkong Sebagai Pembanding Pasar Dire Di Indonesia - Cita Vaga (Universitas Tarumanagara, 2019)
This research aims to understand the history of REITs market in Singapore (S-REITs), Malaysia (M-REITs), Thailand (Thai-REITs), and Hongkong (HK-REITs), along with the curent regulation, with the intention to figure out the differences between markets thus lessons can be learned to boost DIRE’s market in Indonesia. Purpose of this research is to understand the background of REITs growth in Singapore, Malaysia, Thailand, and Hongkong, along with understanding the regulations and differences. By understanding those, one can help to understand how the regulation can help DIRE and invigorate DIRE’s market. Qualitative descriptive model research is done to obtain information as mention above.The conclusion of this research is DIRE have experience the same occurence as other successful REITs market in the region. Regulators have amend the regulations to invigorate the market. While other comparisons have succesfully develop REITs market, DIRE is still stagnan in zero growth condition. Only after comparing the regulations, it is revealed that DIRE’s gearing ratio and income taxes might hinders its growth to be as fast as other comparison. Regulators need to improve these conditions to increase interest towards DIRE.